Optimisation of extraction from Tradescantia zebrina leaves and the gastrointestinal stability of its phytochemicals and bioactivities - Lim, Wey Loon (2025)
Tradescantia zebrina is a medicinal plant traditionally consumed by residents worldwide, which is extensively investigated for its phytochemical contents and bioactivities. However, the effects of gastrointestinal (GI) digestion on the potential health benefits are poorly understood. This study was conducted to optimise the extraction of phytochemical from T. zebrina leaves. The optimal extract was subjected to simulated GI digestion based on the INFOGEST 2.0 protocol. The current study discovered that sequential hybrid extractions were more effective than the individual methods like hot water extraction (HWE) and ultrasonic-assisted extraction (UAE). The “UAE for 20 min, followed by HWE for 15 min” extract was the optimal among all nine treatments, showing the highest total phenolic content (TPC) (8.114 ± 0.007 mg GAE per g dry extract) and total flavonoid content (TFC) (62.56 ± 0.29 mg QE per g dry extract). This extract also recorded the lowest EC50 in 1,1-diphenyl-2-picrylhydrazyl radical (DPPH•) (0.587 ± 0.000 mg/mL) and 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS•+) (1.069 ± 0.003 mg/mL) scavenging activities. Simulated GI digestion significantly reduced TPC and TFC, respectively, to 3.277 ± 0.005 mg GAE and 6.44 ± 0.22 mg QE per g dry extract. Simulated GI digestion also declined the antioxidant and anti-inflammatory activities of the selected T. zebrina extract. The EC50 values of DPPH• and ABTS•+ scavenging activity increased to 2.118 ± 0.042 and 1.585 ± 0.001 mg/mL, respectively. The EC50 values of hydrogen peroxide scavenging activity and inhibition of albumin denaturation increased, respectively, from 1.976 ± 0.006 to 3.658 ± 0.023 mg/mL and from 1.527 ± 0.005 to 2.918 ± 0.023 mg/mL. These changes could potentially proof the negative impacts of human GI digestion, signalling the necessity for strategies that enhance the bioaccessibility.